Improving Speaking Skills: Development Of Speaking Models In Semester II Students Department Of Indonesian Language And Literature Education FBS UNIMA - Pangemanan, N (Journal of Educational Method and Technology, 2019)
The problem with this research is that the second semester students of the Indonesian Language and Literature Education Department are not yet skilled at speaking. The teaching methods provided have not been able to solve the problem. Therefore a learning model is developed which aims to improve speaking skills. The purpose of this study is to describe what efforts can be made to improve the speaking skills of second semester students of the Indonesian Language and Literature Education Department (2018). To describe what learning model can improve the speaking skills of the second semester students of the Indonesian Language and Literature Education Department (2018). The method used in this research is the R&D (Research and Development) method. Of the six parallel classes, the test is only applied to one class because there is no difference in character between one class and another class. The number of students subject to test is 35 people. Quantitative data will be processed using percentage techniques. The value achieved in the pretest before using the model will be compared with the value achieved at the posttest that is after using the model. The results showed that students were ‘quite skilled’ in speaking because the average grade obtained was 7.3. Judging from the aspects assessed, the logical aspect of the proposition, the average grade obtained by students is 8.6. For aspects of text development, the average value obtained is 6.4. For the cohesiveness aspect, the average grade obtained was 8.4. While the aspect of intonation / accent, the average grade obtained is 6.5. It is clear that guided training techniques have not been able to maximize the speaking skills of second semester students, especially the development of texts and intonation / accent. Although the results of the study show that speaking skills have not been maximally achieved by students because they are still below the expected average value (80%), it does not mean that the application of guided training techniques cannot improve students 'speaking skills because the results of the pretest carried out indicate that students' speaking skills are still under the value which is 6. Keywords: Speaking skills; Learning models.